Penguatan Integrasi TIK Dalam Pembelajaran IPA Di Era Pandemi Covid-19 Kepada Guru IPA Di Palangka Raya - Saulim DT Hutahaen; Theo Jhoni Hartanto; Pri Ariadi Cahya Dinata; Dermawati S. (Jurnal Ilmiah Kanderang Tingang, 2021)
The general objective of this strengthening technical guidance program is to provide technical guidance to elementary school teachers on the integration of ICT in science/physics learning in junior high/high school. The specific objectives of this program are to produce (1) a design for integrating ICT in science/physics learning, (2) task packages for integrating ICT in science/physics learning, (3) developing media and teaching materials based on integrating ICT in learning. To achieve the specific objectives of this program, several stages of development were carried out referring to Thiagarajan (1974), known as the Four-D model, namely (1) the Define stage which included analysis of the science/physics curriculum, theoretical assessment of science/physics material, and formulation of science/physics. Physics with appropriate tasks, (2) the Design phase includes: writing ICT integration tasks, and formulating instructions for implementing tasks for teachers and students, (3) the development phase includes: limited trial (two partner teachers), analysis of test results, revision of test results package, and review and evaluation by, and (4) the dissiminate stage includes: expansion of package use test, and monitoring and evaluation of package use. The benefits that can be obtained from this program are: (1) the design package for integrating ICT in science/physics learning can be a guide/examples in learning. (2) the application of ICT integration design packages in science/physics learning can improve teachers' understanding of several ICT integration techniques in learning, and (3) this ICT integration design package in science/physics learning can be recommended to the government, in particular.